Abordagem de gênero sobre a experiência de alunos integrantes do projovem urbano na cidade de Aracaju - Sergipe - Souza, Lucyana Sobral de (2013)
This study sought to examine the relationships that young set with thematic education and work, from the experience of participating in the Urban ProJovem in the city of Aracaju, seeking to capture the social representations for them as built as, highlighting the open possibilities for the expansion of rights and citizenship program participants. Seeking endorse our analyzes weave a dialogue with the theoretical categories: Education, Labor, Qualification, Gender, and Youth. In the case of a public policy of social inclusion based on drug education training and civic education, we are interested in knowing if there is a respect for diversity of your target audience and the recognition that youths experience inequalities members and as such, public policy developed should help to deal with this unequal context. With this intent we favor the development of a quantitative and qualitative study as a methodological option, aiming to capture a volume of information face to face with the public participating in the program, we conducted semistructured interviews with alumni educators the coordinator of the school and the program at the time of its completion. The data analysis allowed us to conclude that despite the innovative proposal in this program, the social representations by young show that basic training and qualifications offered have contradictions that impact on the re/ construction of professional trajectories of so young equitable.